Genome‐wide association study and polygenic risk score analysis for hearing measures in children. Issue 5 (3rd September 2021) - Schmitz, Judith; Abbondanza, Filippo; Paracchini, Silvia
Abstract: An efficient auditory system contributes to cognitive and psychosocial development. A right ear advantage in hearing thresholds (HTs) has been described in adults and atypical patterns of left/right hearing threshold asymmetry (HTA) have been described for psychiatric and neurodevelopmental conditions. Previous genome‐wide association studies (GWASs) on HT have mainly been conducted in elderly participants whose hearing is more likely to be affected by external environmental factors. Here, we investigated HT and HTA in a children population cohort (ALSPAC, n = 6, 743). Better hearing was associated with better cognitive performance and higher socioeconomic status. At the group level, HTA suggested a left ear advantage (mean = −0.28 dB) that was mainly driven by females. SNP heritability for HT and HTA was 0.13 and 0.02, respectively ( n = 4, 989). We found a modest negative genetic correlation between HT and reading ability. GWAS for HT ( n = 5, 344) did not yield significant hits but polygenic risk scores for higher educational attainment (EA, ß = −1, 564.72, p = .008) and schizophrenia (ß = −241.14, p = .004) were associated with lower HT, that is, better hearing. In summary, we report new data supporting associations between hearing measures and cognitive abilities at the behavioral level. Genetic analysis suggests shared biological pathways between cognitive and sensory systems and provides evidence for a positive outcome of genetic risk for schizophrenia.